(3efGaY GdMjhGfs - (3Ydj Hf eMeO Hf YHO GdYRjR Hf aJhM GdKYdHj GdTGaYqj, JGL GdOjf, GdeYQha H` GHf GdOQjge hH` GHf CHj GdNjQ,J (B762 (3g` s
(3ChdgG (B:s
(3LeLeI GdEfSGf GdbOjeI , EPG OafJ ai HQL MeGe cKQ fSdg , hHUGbI jfaY ef dOZ GdghGe hGdbhGHi hGdJGdjd EPG Wdi YdjgG bHd GdZOGA hjLdi CjVkG GdBKGQ GdShO , hHUGbI Se dLejY GdMjhGf s
(3BNQgG (B:s
(3agPG eG hLOfGg ef efGaY CYVGA GdMjhGf GdPi PcQg GdCWHGA heG ESJNHQfGg hLQHfGg hCNPfGg Yf GdKbGJ , aCeG eG PcQ ef GdefGaY GdTGPI ai GdCehQ GdWdSejI hGdSMQjI heGOhfg CUMGH UfYI GdcjejGA ef efGaY s
(3HgG QShe hCTcGd GdMjhGfGJ HdG CdhGfs
(3fSNI NRGFfjIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B6 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B210 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B723s
Keywords: (3GdeYGQa GdYGeIs